ANALISIS TEKNOEKONOMI ALAT PENYEMBELIHAN AYAM UNTUK MENDUKUNG IMPLEMENTASI SISTEM JAMINAN HALAL - Sucipto Sucipto; Riska Indra Wardani; Muhammad Arif Kamal; Danang Triagus Setiyawan (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Halal certified animal slaughtering is urgent to implement and develop. The halal of chicken meat is determined by halal control point (HCP) in the production process, production capacity, and selection of slaughtering equipment. Many chicken slaughterings have not been halal certified because their production equipments do not yet support the application of the Halal Assurance System (HAS). The study aimed to analyse HCP in the production process, the techno-economic analysis of small and medium chicken slaughtering to support HAS implementation. The results showed that with the technical aspect of the medium-scale chicken meat production had HCP at the stage of hanging, stunning, and slaughtering, while the small-scale production of chicken meat had HCP at the slaughtering stage and the collection of slaughtered until perfectly death chickens. Economically, medium-scale slaughtering simulation results of capacity increased to 3,000 chickens per day can use shackle conveyor; thus, reducing Cost of Goods Manufactured (COGM) becomes IDR 22,029 and selling price become IDR 28,638 per chicken. Besides that, small scale slaughtering with a simulated capacity increase of 300 chickens per day with the addition of simple shackle to overcome HCP collection of post-slaughtering. This condition caused the COGM to be IDR 22,016 and the selling price is IDR 28,621 per chicken. In general, the choice of chicken slaughtering equipment according to production capacity will help the implementation of HAS to obtain a competitive product efficiently. Keywords: slaughtering, equipment, chicken, capacity, HCP, Halal Assurance System